Altered Functional Connectivity Strength at Rest in Medication-Free Obsessive-Compulsive Disorder. (8th September 2021) - Lv, Dan; Ou, Yangpan; Wang, Yuhua; Ma, Jidong; Zhan, Chuang; Yang, Ru; Chen, Yunhui; Shang, Tinghuizi; Jia, Cuicui; Sun, Lei; Zhang, Guangfeng; Sun, Zhenghai; et al.
Abstract : Background . Previous studies explored the whole-brain functional connectome using the degree approach in patients with obsessive-compulsive disorder (OCD). However, whether the altered degree values can be used to discriminate OCD from healthy controls (HCs) remains unclear. Methods . A total of 40 medication-free patients with OCD and 38 HCs underwent a resting-state functional magnetic resonance imaging (rs-fMRI) scan. Data were analyzed with the degree approach and a support vector machine (SVM) classifier. Results . Patients with OCD showed increased degree values in the left thalamus and left cerebellum Crus I and decreased degree values in the left dorsolateral prefrontal cortex, right precuneus, and left postcentral gyrus. SVM classification analysis indicated that the increased degree value in the left thalamus is a marker of OCD, with an acceptable accuracy of 88.46%, sensitivity of 87.50%, and specificity of 89.47%. Conclusion . Altered degree values within and outside the cortical-striatal-thalamic-cortical (CSTC) circuit may cocontribute to the pathophysiology of OCD. Increased degree values of the left thalamus can be used as a future marker for OCD understanding-classification.